Factors associated with bleeding outcome of non-vitamin K antagonist oral anticoagulants at a tertiary hospital in Thailand - Limprasert, Sarawuth; Boonmuang, Pornwalai; Rungprai, Daraporn; Meela, Wanrada; Sawatwong, Vasinee; Chaianan, Sireethorn; Pongprasert, Rattapong (Science, Engineering and Health Studies, 2021)
This retrospective descriptive study aimed to evaluate the factors influencing bleeding in patients who received non-vitamin K antagonist oral anticoagulants (NOACs) at Phramongkutklao Hospital, Bangkok, Thailand, from January 2015 to February 2019. A total of 416 patients were included in the study. The median age was 73 years, and the median weight was 66.4 kg. NOACs were prescribed for stroke prevention in nonvalvular atrial fibrillation in the majority of the patients. Hypertension, dyslipidemia, and diabetes mellitus were respectively found in 76.2%, 59.9%, and 29.8% of the patients. Among the patients, 126 (30.3%) received dabigatran, 179 (43.0%) received rivaroxaban, 109 (26.2%) received apixaban, and 2 (9.4%) received edoxaban. Bleeding occurred in 39 patients (9.4%), including 22 (5.3%) in the rivaroxaban group, 12 (2.9%) in the dabigatran group, and 5 (1.2%) in the apixaban group. The most common bleeding type was minor bleeding. Age and previous bleeding history were factors that appeared to influence the increased bleeding outcome of NOACs. Therefore, healthcare providers should prescribe NOACs with care and closely monitor bleeding events in the elderly and patients with prior bleeding history.